Evaluation of Cytotoxicity and Acute Oral Toxicity of Saline Extract and Protein-Rich Fraction from Moringa oleifera Lam. Leaves - Robson Raion de Vasconcelos Alves; Alisson Macário de Oliveira; Gabryella Borges dos Prazeres; Abdênego Rodrigues da Silva; Franciele Florencio Costa; Bárbara Rafaela da Silva Barros; Talita Giselly dos Santos Souza; Luana Cassandra Breintenbach Barroso Coelho; Cristiane Moutinho Lagos de Melo; Magda Rhayanny Assunção Ferreira; Luiz Alberto Lira Soares; Cristiano Aparecido Chagas; et al. (MDPI AG, 2024)
Moringa oleifera Lam. (horseradish tree) leaves demonstrate high nutritional value, are rich in proteins, and are widely used in folk medicine and food. This study investigated the presence of secondary metabolites and antinutritional proteins in leaf extract (LE) and the protein-rich fraction (PRF) derived from M. oleifera leaves, as well as the cytotoxicity to human cells, hemolytic activity, and in vivo acute toxicity and genotoxicity in mice. The flavonoids rutin and vitexin as well as trypsin inhibitors and lectins were detected in LE and PRF. Neither sample demonstrated toxicity against human peripheral blood mononuclear cells and both showed low hemolytic action. In vivo, LE and PRF did not show antinutritional effects and caused no death. The hematological parameters of the animals in the treated group were similar to those of the control. A significant increase in the serum levels of alanine aminotransferase and a discrete leukocyte infiltration with cytoplasmic vacuolization of the hepatocytes in the liver were detected in LE-treated animals. The preparations were not genotoxic or mutagenic. This study shows that LE and PRF are not antinutritional agents and presented low acute toxicity and no genotoxicity or mutagenicity. The present study contributes to the determination of the safety of using M. oleifera leaf proteins.